Pectin and Xylan Biosynthesis in Poplar: Implications and Opportunities for Biofuels Production - Schultz, Joshua A.; Coleman, Heather D. (Frontiers in Plant Science, 2021)
A potential method by which society’s reliance on fossil fuels can be lessened is via the large-scale utilization of biofuels derived from the secondary cell walls of woody plants; however, there remain a number of technical challenges to the large-scale production of biofuels. Many of these challenges emerge from the underlying complexity of the secondary cell wall. The challenges associated with lignin have been well explored elsewhere, but the dicot cell wall components of hemicellulose and pectin also present a number of difficulties. Here, we provide an overview of the research wherein pectin and xylan biosynthesis has been altered, along with investigations on the function of irregular xylem 8 (IRX8) and glycosyltransferase 8D (GT8D), genes putatively involved in xylan and pectin synthesis. Additionally, we provide an analysis of the evidence in support of two hypotheses regarding GT8D and conclude that while there is evidence to lend credence to these hypotheses, there are still questions that require further research and examination.